Integrated traditional Chinese and western medicine modulator for overcoming the multidrug resistance with carbon nanotubes. Issue 87 (20th September 2015) - Zhang, Haijun; Xiong, Jian; Guo, Liting; Patel, Nishant; Guang, Xueneng
<x xml:space="preserve">Abstract</x> GA/Dox/P-gp Ab-CNTs, integrated specific targeting, P-gp inhibitor and chemotherapeutic agent, could represent a promising modulator for overcoming tumor MDR.